Management of blood infection caused by colonization of the vascular port with klebsiella variicola in case of patient treated with palliative chemotherapy - Paulina Kasperska; Małgorzata Nowicka; Eliza Oleksy; Anna Ziółkowska; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2020)
Klebsiella variicola is a bacterial species that was originally identified as a mild endosymbiont in plants, it occurs in humans and cattle. It is a bacterium that has been discovered relatively recently and research on the broader understanding of the pathogen is still underway. Vascular catheters are very often used to receive chemotherapy by patients. The purpose of this work was to present the management of blood infection caused by colonization of the vascular port with klebsiella varicola. The material described can be used to conduct patient pharmacotherapy. Care for a patient with a vascular port should be developed. There is a need to conduct staff training on: proper care and use of the vascular port and Huber needle for pharmacotherapy. Huber needles could be standard material in the list of required equipment in hospital wards to improve patient care with a vascular port.